Typologie des auréoles bocagères en milieu rural - Ion Lucian Ceapraz; Elisa Marraccini; Anne-Maïmiti Dulaurent-Mercadal; Antoine Lacheré; Marie-Cécile Lombart; Sylvane Rava; Anne Combaud (Projets de Paysage)
The grouping of municipalities of the region of Bapaume (in French Communauté de communes de la région de Bapaume) has surveyed its territory in order to define major development needs. The survey includes the peri-urban bocage landscapes which are the interface between urban and farming areas, and are recognised as dependent on local farming activities. To conduct this survey it is necessary to carry out diagnostics of the territories, including semi-natural elements, and in the process to define typologies. The study focuses on comparing two methods for establishing typologies : one based on expertise and the other on statistics. The typologies of the peri-urban bocage landscapes reveal the fact that a majority of municipalities have degraded bocage landscapes. Their state of preservation can not be correlated with technical and economic trends, with typologies of municipalities, or with the presence of road infrastructures. The study reveals the importance of taking into account the historical background of the territory and the shortcomings of a statistical method which does not provide a sufficiently detailed picture of the local landscape.